Management of hair loss diseases - Manabu Ohyama (Wolters Kluwer Medknow Publications, 2010)
The treatment of hair loss diseases is sometimes difficult because of insufficient efficacy and limited options. However, recent advances in understanding of the pathophysiology and development of new remedies have improved the treatment of refractory hair loss conditions. In this article, an update on the management of hair loss diseases is provided, especially focusing on recently reported therapeutic approaches for alopecia areata (AA). An accurate diagnosis is indispensable to optimize treatment. Dry dermoscopy represents new diagnostic techniques, which could enable the differentiation of barely indistinguishable alopecias, e.g. AA and trichotillomania. An organized scalp biopsy adopting both vertical and transverse sectioning approaches also provides a deep insight into the pathophysiology of ongoing alopecias. Among various treatments for AA, intraregional corticosteroid and contact immunotherapy have been recognized as first-line therapies. However, some AA cases are refractory to both treatments. Recent studies have demonstrated the efficacy of pulse corticosteroid therapy or the combination of oral psoralen ultraviolet A therapy and systemic corticosteroids for severe AA. Previous clinical observations have suggested the potential role of antihistamines as supportive medications for AA. Experimental evaluation using AA model mice further supports their effectiveness in AA treatment. Finasteride opens up new possibilities for the treatment of androgenetic alopecia. For androgenetic alopecia patients refractory to finasteride, the combination of finasteride with topical minoxidil or the administration of dutasteride, another 5 alpha-reductase inhibitor, may provide better outcomes. Scarring alopecia is the most difficult form of hair loss disorder to treat. The bulge stem cell area is destroyed by unnecessary immune reactions with resultant permanent loss of hair follicle structures in scarring alopecia. Currently, treatment options for this hair loss disorder are extremely limited. The development of effective therapies for this form of intractable alopecia represents an important issue to be resolved.